New insigths into the diversity of rissoids from sub-antarctic and antarctic waters (Gastropoda: Rissooidea) - Güller, Marina; Zelaya, Diego Gabriel (Polar Biology)
Molluscs have been regarded as one of the most extensively studied and better known marine invertebrates groups in sub-Antarctic and Antarctic benthic communities. In order to test this statement we address here the study of some species of the caenogastropod family Rissoidae, collected during several expeditions to Tierra del Fuego and the Scotia Arc. Currently, the local diversity of this family accounts for a total of 30 species, which were thoroughly revised mostly as part of two monographs. The present study provides new information on shell morphology, radulae and distribution for four of these species: Onoba fuegoensis (Strebel, 1908), O. delecta Ponder, 1983, O. klausgrohi Engl, 2011 and Haurakia averni Ponder and Worsfold, 1994; also contributes to a better understanding of the intraspecific variability of two other species: Onoba schythei (Philippi, 1868) and O. algida Ponder and Worsfold, 1994; and seven new species are described: Onoba clara, O. sandwichensis, O. verrucosa, O. antleri, O. caribu, O. oligochordata, and O. ernestoi. These new findings not only contribute to increase the number of species currently known from the studied area, and provide the first record of a species with multispiral protoconch, and the first record of a bathyal species from southern South America. Furthermore, as part of this study the presence of ?antler-like? marginal teeth is reported for two species, a condition thus far not reported for any other Rissoidae. This study highlights that, even being one of the most intensively studied marine invertebrate groups, molluscs from the Sub-Antarctic and Antarctic waters still remain scarcely known. Fil: Güller, Marina. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Zelaya, Diego Gabriel. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina. ...